Correlation between ossification of the intermaxillary suture and cervical bone maturation in cone beam tomography - Daza Henríquez , José Luis (2026)
Objectives: To determine the relationship between intermaxillary suture ossification and skeletal maturation in cone-beam computed tomography (CBCT) scans. Materials and Methods: This was a descriptive, cross-sectional, retrospective study. A non-probabilistic sample of 300 volumetric scans was used. Intermaxillary suture ossification was assessed using the Angelieri index, while cervical vertebral maturation was evaluated using the Hassel and Farman index. The Spearman’s rho correlation test was applied to analyze the relationship between both variables. Results: Stage C of intermaxillary suture ossification was the most frequent in the studied sample (55%), as well as in each sex and age group, with higher prevalence in females (58.5%) and the 15–21-year age group (63%). For cervical skeletal maturation, stage 4 was the most prevalent (60%), similarly observed in each sex and the two older age groups; however, in the 8–14-year group, stage 3 was more frequent (36.2%). A direct, moderate correlation (p < 0.001; rho = 0.493) was found between intermaxillary suture ossification and cervical skeletal maturation. This association was also observed in each sex (p < 0.001) and age group (p < 0.001), except in the 15–21-year group (p = 0.840). Conclusions: There is a direct and moderate correlation between intermaxillary suture ossification and cervical skeletal maturation.